Meta-Analysis the Effect of School Based Intervention on Smoking in Adolescents - Muhammad Rifqi Azhary; Eti Poncorini Pamungkasari; Yulia Lanti Retno Dewi (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Tobacco is a global problem, in which at least 5 million people die from diseases caused by the consumption of tobacco products such as cigarettes each year, such as cervical cancer, heart disease, gastric ulcers, tuberculosis, kidney failure, pancreas, leukemia, pneumonia, gum and mouth disease as well as lung cancer. This study aims to estimate the magnitude of the effect of School based intervention on cigarette consumption based on the results of a number of previous studies.Subjects and Method: This research is a systematic study and meta-analysis, with PICO as follows Population = junior high school and high school students, Intervention = School based intervention. Comparison = No School based intervention. Outcome = cigarette consumption. The articles used in this study were obtained from several databases including PubMed, ScienceDirect and Google Scholar. This article article was collected for 2 months. The keywords for searching articles are as follows: